High reflectance with steep reflection phase spectrum by guided-mode resonance. (8th November 2016) - Yamada, Katsuaki; Asai, Kosuke; Ko, Yeong Hwan; Kintaka, Kenji; Lee, Kyu Jin; Inoue, Junichi; Ura, Shogo; Magnusson, Robert
Abstract: A guided-mode resonance mirror (GMRM) consisting of a subwavelength grating integrated in an optical waveguide on a highly reflective substrate was predicted to give interesting characteristics of high reflectance with a steep reflection-phase spectrum. This time, the characteristics were experimentally demonstrated for the first time. A GMRM of 1535 nm resonance wavelength was designed and fabricated for a vertically injected wave from the air with TE polarization. The reflectance was measured to be higher than −1 dB over the wavelength from 1520 to 1560 nm. The reflection phase varied by π for a wavelength change of 10 nm.